To be a Bookeater: Literary debate in adolescent reading culture - Grøn, Rasmus; Albrechtslund, Anne-Mette (MedieKultur: Journal of media and communication research, 2020)
Today, adolescent fiction readers are increasingly engaged in different forms of ‘social reading’ in online communities. Through an analysis of Bookeater.dk, a Danish site for adolescent readers, we show how a communal reader identity is constructed via predominant conceptions of reading among the site’s users and how this influences literary value assessment. Overall, the article argues that the young readers’ adherence to this communal identity creates a culture of consensus rather than opening up space for critical discussion about literary value. Neverthe- less, they show critical awareness of the different interests surrounding the publica- tion and promotion of literature.